Exploring partial intrinsic and extrinsic symmetry in 3D medical imaging - Fotouhi, Javad; Taylor, Giacomo; Unberath, Mathias; Johnson, Alex; Lee, Sing Chun; Osgood, Greg; Armand, Mehran; Navab, Nassir (Medical Image Analysis, 2021)
We present a novel methodology to detect imperfect bilateral symmetry in CT of human anatomy. In this paper, the structurally symmetric nature of the pelvic bone is explored and is used to provide interventional image augmentation for treatment of unilateral fractures in patients with traumatic injuries. The mathematical basis of our solution is based on the incorporation of attributes and characteristics that satisfy the properties of intrinsic and extrinsic symmetry and are robust to outliers. In the first step, feature points that satisfy intrinsic symmetry are automatically detected in the Möbius space defined on the CT data. These features are then pruned via a two-stage RANSAC to attain correspondences that satisfy also the extrinsic symmetry. Then, a disparity function based on Tukey's biweight robust estimator is introduced and minimized to identify a symmetry plane parametrization that yields maximum contralateral similarity. Finally, a novel regularization term is introduced to enhance similarity between bone density histograms across the partial symmetry plane, relying on the important biological observation that, even if injured, the dislocated bone segments remain within the body. Our extensive evaluations on various cases of common fracture types demonstrate the validity of the novel concepts and the accuracy of the proposed method.
CRIS-Team Scopus Importer:2023-03-08
Keywords: CT; Image augmentation; Mutual information; Möbius; Robust estimation; Symmetry; Tukey